Urgensi Asbāb Al-Nuzūl Dalam Penafsiran Al-Qur’an: Implementasi Kaidah-kaidah Tafsir dalam Asbāb al-Nuzūl pada Ayat-ayat Hukum: Implementasi Kaidah-kaidah Tafsir dalam Asbāb al-Nuzūl pada Āyah al-Ahkām - El Rahma, Vicky Izza (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This paper will focus on discussing the rules of the Koran interpretation in asbāb al-nuzūl and its implementation in āyah al-ahkām. It’s cause one of the requirements for a person to understand the Koran correctly, especially āyah al-ahkām, is to have a good knowledge of asbāb al-nuzūl. But in the development of the study of interpretation, including in the sub-material asbāb al-nuzūl, there is still very little discussion of the rules of the Koran interpretation.Keyword: Rule of the Koran interpretation, asbāb al-nuzūl, legal verse